1988
DOI: 10.1080/00288233.1988.10423414
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors contributing to the improved lamb survival in Marshall Romney sheep

Abstract: In each of three years (1979, 1980, 1981) 260 -280 mixed age Marshall Romney (MR) and 300 -400 mixed age control Romney (CR) ewes were allocated to eight groups with ewes of each strain present in each group. Four groups were single-sire-mated with four MR rams and the other four groups with four CR rams. A new selection of rams was used each year. The haemoglobin type of all ewes and rams was determined. Ewes were weighed 3 -4 weeks before the beginning of lambing and their respective weights adjusted to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
23
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 29 publications
(36 reference statements)
10
23
1
Order By: Relevance
“…As a matter of fact, prolonged labour can increase the possibility of brain trauma and hypoxia in the neonate [96] and therefore impair suckling, locomotor activity and thermoregulation [20,97,98]. Similar responses are seen in 'easy-care' Romney ewes [99].…”
Section: Selecting For Better Mothersmentioning
confidence: 49%
“…As a matter of fact, prolonged labour can increase the possibility of brain trauma and hypoxia in the neonate [96] and therefore impair suckling, locomotor activity and thermoregulation [20,97,98]. Similar responses are seen in 'easy-care' Romney ewes [99].…”
Section: Selecting For Better Mothersmentioning
confidence: 49%
“…In that study, the SR was higher in lambs of 3-and 4-year-old ewes and lower in lambs of 2-and 5-year-old ewes. Knight et al (1988) also reported a quadratic effect of ewe age on lamb survival that increased in concert with increasing ewe age up to 5 years and then declined rapidly for 6-year-old ewes. Lower SRs for lambs from the youngest ewes could be explained by weaker prenatal nutrition due to young ewes being smaller and/or still developing in addition to providing poorer postnatal maternal care that may lead to hypothermia (Berger, 1997).…”
Section: Survival Rates Of Lambsmentioning
confidence: 97%
“…A study of lambing sites found that preferred features included elevated areas, ditches, banks, scattered trees, logs and boundary fences, and that British sheep were more likely than Merinos to lamb near these features (Alexander et al 1990). Knight et al (1988) observed that lambing sites often provided some shelter from the wind such as hollows, banks, tussocks or the lee of a rise.…”
Section: Effective Design and Location Of Sheltermentioning
confidence: 99%